Growing up without violence (GWV): Results of a cluster randomised trial of a school-based intervention preventing adolescent sexual abuse and exploitation in Brazil - Ligia Kiss; Marto Leal; Ana Paula Portella; Heloína Paiva; Agnese Iuliano; Malini Pires; Helen Shipman; Elizabeth Anderson; Yuki Lo; Ligia Kerr; Carl Kendall; Dario Brito Jr; et al. (PLoS ONE, 2026)
Introduction Child sexual abuse and exploitation (CSAE) are pervasive problems that significantly affect the health of children and adolescents. This paper presents the results of a cluster randomised controlled trial (cRCT) evaluating a school-based intervention designed to prevent CSAE in Brazil through education. Methods We conducted a two-arm cRCT with parallel assignment in two Brazilian municipalities. Sixty schools were randomly allocated to intervention and control arms (30 per group) using stratified randomisation based on municipality and school type (municipal and state-run). We invited 50 randomly selected students, aged 12–17, from each school to complete surveys at baseline and endline. Teachers enrolled in GWV training completed an implementation questionnaire. Our primary analysis focused on a cross-sectional comparison of students’ CSAE risk knowledge between control and intervention schools. Results We found no statistically significant difference in adolescents’ CSAE risk knowledge between the study arms (adjusted mean difference: 0.02, 95% CI −0.19 to 0.23, p = 0.87). There was borderline evidence of interaction by gender, with a greater difference in knowledge scores among girls (p = 0.032). No significant association was found between the number of GWV components implemented and knowledge scores. Discussion Several factors may contribute to this result: the intervention might not have been implemented with sufficient fidelity or intensity, the true effect of GWV could be minimal and below the study's detection threshold, the intervention may have influenced outcomes that were not measured, or the intervention may simply lack effectiveness. Further rigorous evaluations and implementation studies are essential to ensure that resources are directed toward effective strategies. Trial registration The American Economic Association’s registry for randomised controlled trials (AEA RCT Registry). RCT ID: AEARCTR-0011299, https://www.socialscienceregistry.org/trials/11299